Concentration Effect of Leaf Extract from Kekara Laut (Canavalia Maritima Thou.) in inhibiting of Staphylococcus Epidermidis Bacteria with a Statistical Science Approach - Idrus, Irman; Kurniawan, Fajar; Mustapa, Faizal; Wibowo, Dwiprayogo (Indonesian Journal of Chemical Research, 2021)
Importantly to study the coastal vegetation from Kekara Laut (Canavalia maritima Thou.) to observe the antibacterial agents towards Staphylococcus epidermidis. The purpose of this study to examine the variation concentration effect of an ethanol leaf extract from Canavalia maritima Thou. in inhibiting the growth of S. epiderimidis bacteria. The leaf of Canavalia maritima Thou. was prepared using a physicochemical method to obtain ethanol extract, then varied in several concentrations, namely 5% w/v; 10% w/v; 15% w/v; and 20% w/v. Based on these results, we obtain the ethanol leaf extract can inhibit the growth of S. epidermidis with a concentration of 15% w/v for 24 hours having an inhibition zone of 17.17 mm. The statistical analysis test was very significantly different from all antibacterial tests, the value of F count was 682.1 with F table (3.48), at the level of Î± = 0.05 (3.48) and Î± = 0.01 (5.99), which indicates that H0 is rejected, but using the Variance method in the Newman-Keuls range approach shows that each concentration has a good inhibitory ability. The use of Canavalia maritima Thou. leaf extract in low concentrations can significantly inhibit bacterial growth (bacteriostatic).